EXPLORING SIGNIFICANT ASPECTS AND IGNITION OF NATIONALISM IN THE SIGHT OF A CHILD-YOUTH ORGANISATION, ‘MANIMELA’ - Ghosh, Gargi Sen (International Journal of Research -GRANTHAALAYAH, 2025)
In quasi inference nationalism means an association of endearment and inclination towards a nation, it represents an intact nexus and also dedicates a name of the connexion between a nation and its people. Quite indisputably the axiomatic multidimensional approaches of transnational, polyglot, multi-culture and eco-geographical factors have confirmed many aspects of Indian Nationalism. It is easy to say but hard to cultivate the process of resounding implementation of nationalism by delegating appropriate variations and beading them for the creation of a symphony. In 1940, 15th April a renowned child litterateur Bimal Ghosh (Moumachi) had established first registered all India child-youth organisation called ‘Manimela’ (Rabindro Sarovar Stadium, Block-2, Kol. 700029). This has many constituted branch units in various parts of the country and any boys and girls (up to 16 years) irrespective of their caste-creed or religion can join it. It has work for a complete development of children and preparing them to practice the activities which supplemented the basis of nationalism like the contemplation of social harmony and predilections, be honorific about every religious life style and social traditions and pursuing the norms of our great national leaders and typifications etc. I would like to construct a viewpoint about since the beginning what major changes have reflected in the moves and pervasion of this organisation? How far it has successfully maintained its institutional ambitions? In what extent its constructive phases can be enhanced to four-square the sense of nationalism in the young minds? So, if an enlarged discourse has been made on this organisation that would be a unique premise regarding the thoughts and implications of Indian nationalism.